QURANIC ELABORATION OF THE INTERPRETATION OF HUMAN RIGHTS VERSES - Siti Ngainnur Rohmah; Nur Rohim Yunus; Refly Setiawan (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Basically, human rights in Islam are centered on five main things which are summarized in al-dloruriyat al-khomsah or also called al-huquq al-insaniyah fi al-islam (human rights in Islam). This concept contains five main things that must be guarded by every individual, namely hifdzu al-din (respect for religious freedom), hifdzu al-mal (respect for property), hifdzu al-nafs wa al-'ird (respect for the soul, rights to life and individual honor) hifdzu al-'aql (respect for freedom of thought) and hifdzu al-nasl (the obligation to protect offspring). Every human being has basic (fundamental) rights that cannot be revoked and relinquished simply because of differences in race, skin color, religion, gender, language, politics, nationality, and other statuses. Islam as a universal religion has taught the importance of human rights in general regardless of religion, race, ethnicity, and language. In writing this writing using qualitative research methods with a literature approach. The results of the research in this article provide an explanation regarding human rights in the Koran along with the interpretation and protection of human rights law according to the interpretation of the Koran which is in accordance with Islamic teachings.